Analysis of the Cost-Effective Road Maintenance Program for the Improvement of Road Value in Kabupaten Gresik Using the Forecasting Method - Astuti, Dhiannita Tri; Wiguna, I Putu Artama (Institut Teknologi Sepuluh Nopember, 2020)
Roads have a very significant role in enhancing various fields as part of the national transport network. Road management includes road construction, improvement, and technical maintenance activities, which are continuously carried out for the physical maintenance of the road. The role of the road service must be fulfilled so as not to compete with the transportation that passes on the road. Based on the phenomena that have been described, we present the analysis of the cost requirements and methods of road handling in addition to the effectiveness of road stability for the next two years. The research was carried out for a case study of the district major road in Gresik Regency, which is represented in this situation by three main roads. The analysis of a data set is based on the variables of historical data. Then, we analyze using time series with moving averages, exponential smoothing, and trend projection. Next, the method for setting a maintaining strategy of overcoming prediction and its relation to the solidity of the roads, using fuzzy tahani. The results analyzed are confirmed by the recommended output for the next two years.